2015
DOI: 10.1111/poms.12296
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Discount Vouchers in Market with Customer Valuation Uncertainty

Abstract: Online discount voucher market In the discount voucher market, customers usually face two types of valuation uncertainty, namely, preference uncertainty and consumption state uncertainty. Preference uncertainty is related to the customer's lack of relevant experience with the merchant, whereas consumption state uncertainty is related to the advance selling nature of the discount voucher mechanism. By taking a comprehensive perspective (i.e., considering revenue management and promotion effect at the same time)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Groupon is a famous daily deal website. Gao and Chen [14] said " ese online voucher vendors sell vouchers in specific cities at discounts ranging from 50% to 90%. ese vouchers are typically offered by local businesses, such as restaurants and spas."…”
Section: Literature Reviewmentioning
confidence: 99%
“…Groupon is a famous daily deal website. Gao and Chen [14] said " ese online voucher vendors sell vouchers in specific cities at discounts ranging from 50% to 90%. ese vouchers are typically offered by local businesses, such as restaurants and spas."…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, product quality or value is most likely to be the future‐oriented consumers' concern because these directly affect the purchasers' expected utility. Thus, we define a discount factor α that represents the degree of quality or value perception of new products for the informed consumers faced with an advance price discount (i.e., α ∈(0,1]) (Gao & Chen, ; Li et al, ; Kwon & Weingart, ; Su & Zhang, ). Here, we first assume that the value discount factor is an independent variable; then, we will extend to the cases in which it varies across consumers or depends on the advance price discount.…”
Section: Model Developmentmentioning
confidence: 99%
“…Edelman et al (2016) [13] investigated the pro tability, pricing discrimination, and advertising e ect of discount vouchers. Gao and Chen (2015) [14] found that no show of voucher buyers could be good for (large or start-up) sellers. Ni et al (2015) [15] studied the optimal pricing strategy of sellers by classifying customers into collectivist and individualistic customers according to actual market information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, as a platform for implementing group-buying, the corresponding websites should receive greater attention. The mechanism of GBW experienced the evolution from dynamic pricing model (e.g., [6{8]) to xedpricing model (e.g., [14,15,17]). The dynamic model focuses on the quantity and pricing scheme, that is, the greater the quantity, the lower the price.…”
Section: Literature Reviewmentioning
confidence: 99%